Peran media digital dalam penguatan moderasi beragama di kalangan mahasiswa - Annur, Zulfadhli (Maliki Interdisciplinary Journal, 2026)
This article discusses the role of digital media in strengthening religious moderation among university students in the digital era. The study aims to explain how social media can be used as a medium for internalizing values of tolerance, anti-radicalism, and respect for diversity. The research method used is a qualitative literature review by analyzing scientific journals related to religious moderation and digital media. The findings indicate that digital media plays an important role in creating dialogue spaces, disseminating educational content, and improving students’ digital literacy. However, digital media also presents challenges such as hoaxes, hate speech, and the spread of radical ideologies. Therefore, strengthening religious moderation education and digital literacy is necessary so that students can use digital media wisely and responsibly.